(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The article discusses the interdependence of moral and social education in preschool age. It is proved that these two directions of pedagogical activity are inextricably linked and have a mutual influence on each other. The importance of the purposeful formation of moral qualities (kindness, honesty, justice) and social skills (communication, cooperation, empathy) in preschoolers is emphasized. implementation of interrelated moral and social education in preschool education.